AGR2-AGR3 hetero-oligomeric complexes: Identification and characterization - Černocká, Hana; Vonka, Petr; Kasalová, Veronika; Sommerova, Lucia; Vandova, Veronika; Hrstka, Roman; Ostatna, Veronika (Bioelectrochemistry, 2021)
In this paper we compare electrochemical behavior of two homolog proteins, namely anterior gradient 2 (AGR2) and anterior gradient 3 (AGR3), playing an important role in cancer cell biology. The slight variation in their protein structures has an impact on protein adsorption and orientation at charged surface and also enables AGR2 and AGR3 to form heterocomplexes. We confirm interaction between AGR2 and AGR3 (i) in vitro by immunochemical and constant current chronopotentiometric stripping (CPS) analysis and (ii) in vivo by bioluminescence resonance energy transfer (BRET) assay. Mutation of AGR2 in dimerization domain (E60A) prevents development of wild type AGR2 dimers and also negatively affects interaction with wild type AGR3 as shown by CPS analysis. Beside new information about AGR2 and AGR3 protein including their joint interaction, our work introduces possible applications of CPS in bioanalysis of protein complexes, including those relatively unstable, but important in the cancer research.
Keywords: Carrier Proteins; Oncogene Proteins; multimerizace proteinu; lidé; Protein Structure, Quaternary; transportní proteiny; Protein Multimerization; adsorpce; Humans; Adsorption; Protein Domains; kvarterní struktura proteinů; Mucoproteins; Neoplasm Proteins; onkogenní proteiny; molekulární modely; proteinové domény; nádorové proteiny; Models, Molecular; mukoproteiny